Factors Associated with Electricity Losses: A Panel Data Perspective - Briseño, Hugo; Rojas, Omar (International Journal of Energy Economics and Policy, 2020)
Electricity losses are an important problem worldwide that shuld be mitigated, since they generate an impact on CO2 emissions and drive a possible rate increase. The benefits of the reduction of such losses are savings, a better environment and less infrastructure needs, amongst others. However, in order to generate reductions, it is imperative to measure the factors associated with such losses. Thus, the objective of this study is to explore the factors associated with electricity losses in the world. A database of 91 countries and 10 years of available data, from 2005 to 2014, was built, with variables taken according to our literature review and obtaind from different publicly available sources. A panel data model with international information was then tested in order to find the determinants of power losses. The model with the best fit was one with random effects. Our results show that the variables unemployment and crime were significant and positive at one percent, while urbanization and education were significant and negative also at one percent. Finally, we provide some policy implications on the evidence of how electricity losses are associated with low education, high unemployment, high homicide rates, and less urbanization. Keywords: Electricity losses, T&D losses, electricity theft, non-technical losses, power losses, random effects. JEL Classifications: L94, N70, Q41 DOI: https://doi.org/10.32479/ijeep.9599